2020
DOI: 10.29303/jppipa.v6i2.427
|View full text |Cite
|
Sign up to set email alerts
|

Development of Problem-Based Learning Student Worksheets to Facilitate Students’ Problem Solving Skills

Abstract: The purpose of this study was to develop Problem-Based Learning student worksheets on bioremediation material to facilitate students authentic problem solving skills. The development used a procedural development model called ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were Biology Students at Surabaya State University. Data collection used validation, observation, and test techniques. Student worksheets quality measurement obtained by a rating scale instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…This statement is in accordance with the results of research conducted by Sanggara (2018) which states that students' problem-solving abilities can be significantly improved by practical learning. The results of other research regarding problem solving skills were also found by Wahyuni, (2020) stating that students' problem solving skills can be developed by learning using worksheets so that they are practical and effective in learning well.…”
Section: Resultsmentioning
confidence: 84%
“…This statement is in accordance with the results of research conducted by Sanggara (2018) which states that students' problem-solving abilities can be significantly improved by practical learning. The results of other research regarding problem solving skills were also found by Wahyuni, (2020) stating that students' problem solving skills can be developed by learning using worksheets so that they are practical and effective in learning well.…”
Section: Resultsmentioning
confidence: 84%
“…One of the strategies used is to create worksheets based on higher-order thinking skills. As developed by Wahyuni et al (2020), worksheets are developed to facilitate authentic problem-solving skills of students in the learning process. The goal of students' worksheet-based higher-order thinking skills is to explore students' high-level thinking skills, and each question is prepared by paying attention to indicators and aspects of scientific creativity skills, critical thinking, and creative thinking (Astutik et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the demands of instructional materials, particularly student worksheets, is the goal of this study, which needs to be developed in the material of additives and addictive substances for class VIII through initial observation sheets needs, questionnaires and interviews with teachers. such as research conducted by (Nabila, 2022;Wahyuni et al, 2020;Yakin, 2021) that PBL-based electronic student worksheets can improve problemsolving abilities.…”
Section: Introductionmentioning
confidence: 99%